New findings of light dusky rockfish Sebastes variabilis (Sebastidae) at the eastern coast of Kamchatka - Yu. K. Kurbanov (Известия ТИНРО, 2020)
Light dusky rockfish Sebastes variabilis is a rare fish species in the waters at East Kamchatka, rarely recorded in trawl catches. They aggregate in the areas with complicated bottom topography and active water dynamics with the depth from 118 to 316 m. Their maximum catches are recorded off Capes Gowen, Olyutorsky, and Kronotsky. The light dusky rockfish body length varies from 34 to 50 cm, and body weight — from 0.53 to 1.78 kg. Some issues related to the migration routes of this species to the shores of Kamchatka are discussed.